Strain-induced direct-indirect bandgap transition and phonon modulation in monolayer WS2 - Wang, Yanlong; Cong, Chunxiao; Yang, Weihuang; Shang, Jingzhi; Peimyoo, Namphung; Chen, Yu; Kang, Junyong; Wang, Jianpu; Huang, Wei; Yu, Ting (Nano research, 2015)
In situ strain photoluminescence （PL） and Raman spectroscopy have been employed to exploit the evolutions of the electronic band structure and lattice vibrational responses of chemical vapor deposition （CVD）-grown monolayer tungsten disulphide （WS2） under uniaxial tensile strain. Observable broadening and appearance of an extra small feature at the longer-wavelength side shoulder of the PL peak occur under 2.5% strain, which could indicate the direct-indirect bandgap transition and is further confirmed by our density-functional-theory calculations. As the strain increases further, the spectral weight of the indirect transition gradually increases. Over the entire strain range, with the increase of the strain, the light emissions corresponding to each optical transition, such as the direct bandgap transition （K-K） and indirect bandgap transition （F-K, ≥2.5%）, exhibit a monotonous linear redshift. In addition, the binding energy of the indirect transition is found to be larger than that of the direct transition, and the slight lowering of the trion dissociation energy with increasing strain is observed. The strain was used to modulate not only the electronic band structure but also the lattice vibrations. The softening and splitting of the in-plane E＇ mode is observed under uniaxial tensile strain, and polarization-dependent Raman spectroscopy confirms the observed zigzag-oriented edge of WS2 grown by CVD in previous studies. These findings enrich our understanding of the strained states of monolayer transition-metal dichalcogenide （TMD） materials and lay a foundation for developing applications exploiting their strain-dependent optical properties, including the strain detection and light-emission modulation of such emerging two-dimensional TMDs.